2021
DOI: 10.1038/s42003-021-02054-9
|View full text |Cite
|
Sign up to set email alerts
|

ARP-T1-associated Bazex–Dupré–Christol syndrome is an inherited basal cell cancer with ciliary defects characteristic of ciliopathies

Abstract: Actin-Related Protein-Testis1 (ARP-T1)/ACTRT1 gene mutations cause the Bazex-Dupré-Christol Syndrome (BDCS) characterized by follicular atrophoderma, hypotrichosis, and basal cell cancer. Here, we report an ARP-T1 interactome (PXD016557) that includes proteins involved in ciliogenesis, endosomal recycling, and septin ring formation. In agreement, ARP-T1 localizes to the midbody during cytokinesis and the basal body of primary cilia in interphase. Tissue samples from ARP-T1-associated BDCS patients have reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…It occurs in the second or third decade of life and is caused by mutations in the CYLD gene, located on chromosome 16q12-16q13 [ 32 , 46 ] Bazex-Dupré-Christol syndrome (BDCS). It is a dominant genetic disorder linked to chromosome Xq24-Xq27.1 caused by a gene mutation in the actin-related protein-testis 1 (ARP-T1/ACTRT1) gene, characterized by multiple BCCs, follicular atrophy on the back of the hands and feet (resembles the skin and is different from the palm-plantar pits of the NBCCS), hypohidrosis, and hypotrichosis [ 47 , 48 ] Rombo syndrome. It is a dominant hereditary disease like Bazex-Dupré-Christol syndrome, reported in a single family.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs in the second or third decade of life and is caused by mutations in the CYLD gene, located on chromosome 16q12-16q13 [ 32 , 46 ] Bazex-Dupré-Christol syndrome (BDCS). It is a dominant genetic disorder linked to chromosome Xq24-Xq27.1 caused by a gene mutation in the actin-related protein-testis 1 (ARP-T1/ACTRT1) gene, characterized by multiple BCCs, follicular atrophy on the back of the hands and feet (resembles the skin and is different from the palm-plantar pits of the NBCCS), hypohidrosis, and hypotrichosis [ 47 , 48 ] Rombo syndrome. It is a dominant hereditary disease like Bazex-Dupré-Christol syndrome, reported in a single family.…”
Section: Main Textmentioning
confidence: 99%
“…Bazex-Dupré-Christol syndrome (BDCS). It is a dominant genetic disorder linked to chromosome Xq24-Xq27.1 caused by a gene mutation in the actin-related protein-testis 1 (ARP-T1/ACTRT1) gene, characterized by multiple BCCs, follicular atrophy on the back of the hands and feet (resembles the skin and is different from the palm-plantar pits of the NBCCS), hypohidrosis, and hypotrichosis [ 47 , 48 ]…”
Section: Main Textmentioning
confidence: 99%
“…Germline inactivation of one copy of the Hh receptor Patched 1 (PTCH1) gene [36] and, more rarely, of PTCH2 [37], or of Suppressor of Fused (SUFU) [38], followed by the somatic loss of the second allele results in Gorlin syndrome [12] that are frequently observed in BCC patients. Furthermore, UV-induced mutations of genes encoding for Hh pathway components were identified in about 85% of sporadic BCCs [33,[39][40][41][42][43][44]. Based on this evidence, the Hh pathway has become a major target for molecular therapies aimed to inhibit BBC growth, mainly through the inactivation of the Hh effector SMO (i.e., vismodegib, sonidegib, patidegib, and itraconazole) [45].…”
Section: Mutational Patternmentioning
confidence: 99%
“…It has been reported that primary cilia are not formed in many types of malignant tumors to dampen cilia-related signal transduction ( Seeley et al, 2009 ; Hassounah et al, 2013 ; Nobutani et al, 2014 ; Liu et al, 2019 ). However, certain types of medulloblastoma, gastrointestinal stromal tumor, and basal cell carcinoma retain the primary cilia, which transduce signals such as Hedgehog and Wnt to contribute to the malignancy ( Hassounah et al, 2012 ; Castiella et al, 2013 ; Park et al, 2021 ; Marino, 2022 ; Youn et al, 2022 ). Thus, whether primary cilia promote or suppress the progression of carcinoma is an important but difficult question in the field of oncology.…”
Section: Introductionmentioning
confidence: 99%